Diversity of heterocystous cyanobacteria in rice soils - Irisarri, P.; Gonnet, S.; Deambrosi, E.; Monza, J. (Agrociencia Uruguay, 1999)
To evaluate the potential use of nitrogen-fixing heterocystous cyanobacteria as natural biofertizer for rice in Uruguay, the diversity, abundance and variation of these microorganisms along the crop cycle were studied at Paso de la Laguna (Treinta y Tres). Diversity and population density of heterocystous cyanobacteria were compared between a treatment without urea inoculated with cyanobacteria, other with urea application and without inoculum and a control without nitrogen and inoculum. The comercial inoculum used, dry mixture of Nostoc sp. and Tolypothrix tenuis, was applied at two-fold the recommended dosis. CuSO4 (2,5 K/ha) was added to the control treatment pretending to reduce the native cyanobacterial population. About 90 % of the heterocystous cyanobacteria found in all treatments belonged to the genera Anabaena and Nostoc. Anabaena was the dominant genus at the control treatment and Nostoc at the rest of the treatments. The less abundant genera were Calothrix, Cylindrospennum, Nodularia, Scytonema and Tolypothrix. Macroscopic colonies of Gloeotrichia sp. appeared in all the treatments twelve weeks after irrigation started. The highest value of cyanobacteria, 1,6 x 105 CFU/cm2, was found at the control 8 weeks after the irrigation started. At this time of the crop cycle, the highest cyanobacterial numbers were found in all the treatments. The broadcasted application of urea and the inoculation were associated with less cyanobacterial density, 1,6 y 1 x 104 CFU/cm2, respectively.